A case study of unmanned aerial vehicle (drone) technology and its applications in the COVID-19 pandemic - Aabid, Abdul; Perveez, Bisma; Perveen, Nagma; Khan, Sher Afghan; Shabbir, Omar (The Scientific Press, 2022)
Over the last two decades, unmanned aerial vehicles (UAV) or drones have become a vital tool with their enormous applications due to their versatility, agility, and applicability. On the other hand, a soft computing approach such as artificial intelligence (A.I.), the internet of things (IoT), neural network, fuzzy logic, genetic algorithm, and machine learning has become crucial in the design and application of UAVs. The major significance of this work is to introduce the drone during the coronavirus disease 2019 (COVID-19) pandemic hence the technologies, and proposed methods with soft computing in the COVID-19 have been critically analyzed. As a result, a critical analysis of predictable design/models of UAVs used during the COVID-19 pandemic has been established and suggested the research gap for future work.